Step-by-step explanation:
1. (-3/2, 1)
2. (6,-3)
3. (8/3, 2)
4. <u>(</u><u>2</u><u>,</u><u>-4</u><u>)</u>
<u>5</u><u>.</u><u>(</u><u>-3</u><u>,</u><u>-1</u><u>)</u>
<u>6</u><u>.</u><u> </u><u>(</u><u>0</u><u>,</u><u>3</u><u>/</u><u>2</u><u>)</u>
<u>7</u><u>.</u><u> </u><u>(</u><u>4</u><u>,</u><u> </u><u>-2</u><u>)</u>
<u>8</u><u>.</u><u>(</u><u>8</u><u>,</u><u>2</u><u>)</u>
<u>9</u><u>.</u><u> </u><u>(</u><u>0</u><u>,</u><u>0</u><u>)</u>
Answer:
A
Step-by-step explanation:
1/2x-4=-2x-9...u vil get the ans
Answer:
f⁻¹(x) = (1/2)x +5
Step-by-step explanation:
In y = f(x), swap the variables, then solve for y. The expression you get is f⁻¹(x).
... y = 2x -10
... x = 2y -10 . . . . . . swapped variables
... x +10 = 2y . . . . . add 10
... (1/2)x + 5 = y . . . . divide by 2
... f⁻¹(x) = (1/2)x + 5 . . . . . . rewrite using function notation
(3 x 10) x 8 = 3 x (10 x 8)
this is called the associative property of multiplication.
it states : (a * b) * c = a * (b * c)
1/4-1/16=
=1*4/16 - 1*1/16
=4/16-1/16
=3/16
Or 1/8